Foreign direct investment and wage inequality: Evidence from the People's Republic of China - Cen Chen; Hongmei Zhao; Yunbo Zhou (Asian Development Bank Institute (ADBI), 2017)
Based on theoretical analysis of effects of foreign direct investment (FDI) on the wage gap between foreign firms and domestic firms in the host country, we use data from Chinese Industrial Enterprises Database to measure these effects. Theoretical results show that the wage gap between foreign firms and domestic firms in the host country caused by the FDI labor transfer effect and technology spillover effect tends to increase then decrease, which implies an inverted U curve track. The empirical results show that the FDI has significant effects on the wage gap in the People's Republic of China (PRC) during the observed time period. The contribution of the FDI to change of the wage gap is above 10%, which is in the second position among all observed factors. From the overall point of view, the contribution of the FDI tends to decrease. The reason is that the wage gap caused by the FDI has stepped into the decreasing stage. This means the wage gap between foreign firms and domestic firms currently has been on the latter part of the inverted U curve. The Chinese government should expand fields for FDI so as to decrease the wage gap between foreign firms and domestic firms. This policy implication should be helpful for the PRC to step over the "middle-income trap".
Keywords: F23; J31; O15; 330; Foreign Direct Investment; wage inequality; Theil index; Sharpley value decomposition